Does Uncertainty Matter for Trade - Economic Growth Nexus in Indonesia? - Panky Tri Febiyansah; Bintang Dwitya Cahyono; Rio Novandra (Economics and Finance in Indonesia, 2021)
This paper aims to test the impact of uncertainty on the causal relationship among exports, imports, and economic growth in Indonesia. The relationship is constructed by examining the presence of FDI-adjusted exports and imports (trade) and the output link using conditional variances-covariances derived from the generalized autoregressive conditional heteroskedastic (GARCH) process in a vector error correction model (VEC-GARCH model). Using evidence in Indonesia, the model exposes the uni-directional nexus from trade performance to trade-adjusted output growth in the absence of uncertainty. The volatility effects are evident in the causal relationship between trade and output. The finding shows that the uncertainty effects hamper the trade-economic growth nexus. Incorporated with the long-run causality, trade still causes output even after containing the contributions of volatility. The significant role of imports highlights the higher demand for intermediate capital products and the inclusion of technology in strengthening economic growth.